Road Accident of Reptiles by Heavy Traffic Movement in and around Tropical forest Research Institute Campus, Jabalpur, Madhya Pradesh, Central India - Paunikar, Sanjay (Indian Forester, 2014)
Reptiles are one of the important members of the animal kingdom and food chain as a predators and prey for the other animals. Population of reptiles fauna is declining due to number of reasons including road kill by heavy traffic movements on the highways. In the present study total 160 road kills of reptiles (8 families and 18 species) were recorded on roads in and around TFRI campus, Jabalpur. This includes skinks (grass and striped skink), lizards (garden and monitor) and snakes (vipers, kraits, cobra, rat and snakes, etc). The maximum road kills were observed in the month of June-July and minimum August-September. The highest road kills were of serpent (snakes) species. Several road kill species of reptiles come under the Wild Life Protection Act and their status is included in different schedules and IUCN categories.